Effect of replacement of barley with reconstituted bajra grains (Pennisetum typhoideum) and mustard-cake with uromalt-40 on the performance of growing crossbred calves - Kundu, Ramphal; Lohan, O P (The Indian Journal of Animal Sciences, 2012)
A growth trials of 120 days on 16 growing crossbreed calves was conducted to evaluate uromalt-4U and reconstituted bajra grains. The calves were divided in 4 groups having 4 claves in each group and were fed 4 different rations. Group 1 was offered control ration T1 : in T2 barley was replaced with reconstituted bajra grains: in T3 barley was replaced with raw bajra grain, and in T4 group mustard-cake was replaced with uromalt-40. The average DM and CF intake were higher in uromalt-40 fed group. CP, EE and NFE digestibilities were significantly (P